2015
DOI: 10.1371/journal.ppat.1004892
|View full text |Cite
|
Sign up to set email alerts
|

The Recent Evolution of a Maternally-Inherited Endosymbiont of Ticks Led to the Emergence of the Q Fever Pathogen, Coxiella burnetii

Abstract: Q fever is a highly infectious disease with a worldwide distribution. Its causative agent, the intracellular bacterium Coxiella burnetii, infects a variety of vertebrate species, including humans. Its evolutionary origin remains almost entirely unknown and uncertainty persists regarding the identity and lifestyle of its ancestors. A few tick species were recently found to harbor maternally-inherited Coxiella-like organisms engaged in symbiotic interactions, but their relationships to the Q fever pathogen remai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
314
2
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 250 publications
(347 citation statements)
references
References 64 publications
19
314
2
1
Order By: Relevance
“…Other animal and avirulent bacterial models, particularly those suitable for BSL2, represent safer alternatives to investigate how host and bacterial factors interface and affect the pathogenesis of C. burnetii. Here, we present Drosophila as a genetically tractable host model to study Coxiella infection that complements previous work performed in mammalian and other invertebrate models (23)(24)(25). The malleability of the C. elegans and Drosophila models makes them applicable to studies in mammalian systems, and Drosophila can be used to identify novel arthropod genetic variants implicated in susceptibility to C. burnetii infection that have homologous mammalian counterparts.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Other animal and avirulent bacterial models, particularly those suitable for BSL2, represent safer alternatives to investigate how host and bacterial factors interface and affect the pathogenesis of C. burnetii. Here, we present Drosophila as a genetically tractable host model to study Coxiella infection that complements previous work performed in mammalian and other invertebrate models (23)(24)(25). The malleability of the C. elegans and Drosophila models makes them applicable to studies in mammalian systems, and Drosophila can be used to identify novel arthropod genetic variants implicated in susceptibility to C. burnetii infection that have homologous mammalian counterparts.…”
Section: Discussionmentioning
confidence: 88%
“…Although C. burnetii has been detected in tick populations worldwide (19)(20)(21), the role of ticks in the epidemiology of Q fever remains unclear (22). A recent study demonstrated that C. burnetii has emerged from Coxiellalike endosymbiont organisms found in ticks, revealing evidence of how the bacterium evolved from arthropods to infect mammalian cells by the acquisition of virulence factors (23). Another study used larvae of the greater wax moth, Galleria mellonella, to investigate antibiotic efficacy following Coxiella infection and the role of dotA/dotB, two components of the Coxiella T4SS, in establishing infection (24).…”
mentioning
confidence: 99%
“…The phylogenetic origin of C . burnetii is unknown, but new Coxiella -like endosymbionts (CLE) have been isolated from ticks [4, 5]. CLE differ from C .…”
Section: Introductionmentioning
confidence: 99%
“…Adding further complexity, some authors consider Rickettsia species as endosymbionts that are transmitted vertically in arthropods, and only secondarily serve as pathogens of vertebrates [40]. For the Coxiella genus, the species C. burnetii is mostly considered as a vertebrate pathogen while numerous other Coxiella species have been found associated to ticks [41]. Phylogenetic analyses combined with future science group www.futuremedicine.com experimental approaches suggested that these might also be considered as endosymbionts of ticks [11,42].…”
Section: The Technology-driven Revolution Of Tickborne Pathogen's Vismentioning
confidence: 99%